Women’s ombudsman’s office: Prevention of Spousal Violence in Sucre - Choque Arando, Ivonné; Gutiérrez García, Andrea (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research was carried out in eight women’s ombudsmen (two private and six public) with the purpose of characterizing the services they provide and reflecting on the prevention mechanisms they carry out against conjugal violence in the municipality of Sucre - Bolivia. The data collection technique used was the semi-structured interview. The results of the study revolve around three large categories namely: (1) services they provide, (2) characteristics of the beneficiary population and services they request, (3) characteristics of the professionals and their job.